Barcelona. "El primer aniversario de la muerte de B. Durruti: Joaquin Ascaso hablando". Behind him: Pou, Garcia Oliver and Domenech. Copied from CNT collection
Barcelona. "El primer aniversario de la muerte de B. Durruti: Joaquin Ascaso hablando". Behind him: Pou, Garcia Oliver and Domenech. Copied from CNT collection.